2019
DOI: 10.1111/aor.13474
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide incorporated polycaprolactone/chitosan/collagen electrospun scaffold: Enhanced osteogenic properties for bone tissue engineering

Abstract: This in vitro study aimed to evaluate the physicochemical and biological activity of the polycaprolactone/chitosan/collagen scaffolds incorporated with 0, 0.5, 3, and 6 wt% of graphene oxide (GO). Using standard tests and MG-63 cells, the characteristics of scaffolds were evaluated, and the behavior of osteoblasts were simulated, respectively. A non-significant decrease in nanofibers diameter was noted in scaffolds with a higher ratio of GO. The hydrophilicity and bioactivity of the scaffold surface, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 73 publications
0
56
0
Order By: Relevance
“…This study aimed to reinforce CS scaffolds with GO at wt % of 2, 4, and 6 which were further crosslinked with glutaraldehyde (GTA). The highest GO wt % attempted in this study was justified by a recent work by Aidun and coworkers (2019) [ 22 ]. They also prepared their chitosan composite scaffolds with GO at wt % of 6.…”
Section: Introductionmentioning
confidence: 84%
“…This study aimed to reinforce CS scaffolds with GO at wt % of 2, 4, and 6 which were further crosslinked with glutaraldehyde (GTA). The highest GO wt % attempted in this study was justified by a recent work by Aidun and coworkers (2019) [ 22 ]. They also prepared their chitosan composite scaffolds with GO at wt % of 6.…”
Section: Introductionmentioning
confidence: 84%
“…Importantly, they can be combined with inorganic components, such as synthetic HAp, alpha-and beta-tricalcium phosphate (α-and β-TCP) as well as bioactive glass in order to improve their structural similarity to natural bone, mechanical properties, and osteoconductivity [72,256,[260][261][262][263]. [272] For instance, Janarthanan et al [273] fabricated PCL/α-TCP, gelatin/PCL/α-TCP, and fibronectin/PCL/α-TCP scaffolds using solvent casting method combined with gas foaming process. They showed that both gelatin/PCL/α-TCP and fibronectin/PCL/α-TCP scaffolds were characterized by superior biocompatibility in vitro compared to PCL/α-TCP biomaterial (studies on human ASCs).…”
Section: Bone Tementioning
confidence: 99%
“…Since GO also has good antibacterial properties [10,11], it has been used as surgical dressing to prevent infection and heal external wounds [12]. Moreover, a stable structure built by planting phospholipid bilayer on GO [13] can promote cell adhesion [14] and proliferation [15]. Many reports suggest that GO is biocompatible [16] and biostable [17] and hence serves as an interesting platform for biomedical applications [18,19].…”
Section: Introductionmentioning
confidence: 99%